Unrecognized diversity in New Guinean crayfish species (Decapoda, Parastacidae): The evidence from molecular data. Issue 6 (November 2016) - BLÁHA, Martin; PATOKA, Jiří; KOZÁK, Pavel; KOUBA, Antonín
Abstract: The phylogenetic relationships among imported ornamental crayfish belonging to the genus Cherax were inferred from a combined dataset of 3 mitochondrial genes (COI, 16S and 12S) and by comparison with available GenBank sequences of 14 Cherax species. Furthermore, the concordance of previously described species obtained from a wholesaler ( Cherax boesemani, C. holthuisi and C. peknyi ) with available GenBank sequences was verified based on COI with special respect to comparison with sequences assigned as Cherax species. Recently described species C. gherardiae, C. pulcher and C. subterigneus belong to the northern group of Cherax species. Comparison and analysis with other GenBank COI sequences show previously unreported diversity of New Guinean species, suggesting 5 putative new species. Surprisingly, species assigned to the subgenus Astaconephrops do not form a monophyletic clade; this subgenus should be reappraised relative to the purported typical morphological characteristic of the uncalcified patch on male chelae. Increasing importation of crayfish underscores the importance of accurate species identification. Use of basic molecular methods is a necessary requisite for documenting occurrence, abundance and population trends of target species. Consequently, it helps to support eventual conservation decision‐making by stakeholders.